Bovine Lactoferrin Inhibits Adenovirus Infection by Interacting with Viral Structural Polypeptides - Pietrantoni, Agostina (American Society for Microbiology, 2003)
We recently demonstrated that lactoferrin, an antimicrobial glycoprotein, can inhibit adenovirus infection by competing for common glycosaminoglycan receptors. This study further characterizes the antiadenovirus activity of the protein, thus demonstrating that lactoferrin neutralizes infection by binding to adenovirus particles and that its targets are viral III and IIIa structural polypeptides.